Do low serum UCH-L1 and TDP-43 Levels indicate disturbed ubiquitin-proteosome system in autism spectrum disorder? - Çetin, İhsan; Tezdiğ, İhsan; Tarakçıoğlu, Mahmut Cem; Kadak, Muhammed Tayyib; Demirel, Ömer Faruk; Özer, Ömer Faruk; Erdoğan, Fırat; Doğangün, Burak (AVES, 2017)
Introduction: The mechanism of ubiquitination-related abnormalities causing neural development problems is still unclear. We examined the association between autism and serum transactive response DNAbinding protein-43 (TDP-43) and ubiquitin c-terminal hydrolase-L1 (UCH-L1) levels, both of which are members of the ubiquitinproteosome system. Methods: We measured serum levels of TDP-43 and UCH-L1 in 24 children with autism and 24 healthy children. Childhood Autism Rating Scale (CARS) was used to assess symptom severity at admission. Results: The mean serum TDP-43 and UCH-L1 levels in children with autism spectrum disorder (ASD) were found to decrease compared to healthy controls (p< 0.001, 506.21 +/- 780.97 ng/L and 1245.80 +/- 996.76 ng/L, respectively; 3.08 +/- 5.44 ng/mL and 8.64 +/- 6.67 ng/mL, respectively). A positive correlation between serum TDP-43 levels and UCH-L1 levels was found in the ASD group (r= 0.947, n= 24, p< 0.001). The CARS score of children with ASD was 48.91 points (standard deviation [SD]: 5.82). Conclusion: Low serum levels of UCH-L1 and TDP-43 may reflect disturbed ubiquitination in autism.

Amaç: Protein ubikitinlenme ile ilgili bozuklukların nöronal gelişim sorunlarına nasıl yol açtığı açıklanamamıştır. Bu çalışmada, ubikuitin proteozom sistemine üye olan ubikuitin c-terminal hidrolaz-L1 (UCH-L1) ve transaktif yanıtlı DNA-bağlayıcı protein (TDP-43) düzylerinin otizm ile ilişkisi araştırılmıştır.Yöntemler: Bu bağlamda 24 otizm tanılı çocuk ve 24 sağlıklı çocukta serum TDP-43 ve UCH-L1 düzeylerine bakılmıştır. Otizm şiddet derecesi Çocukluk Otizm Derecelendirme Ölçeği (ÇODÖ) ile değerlendirilmiştir. Bulgular: Otizm tanılı çocukların başvuru sırasında ortalama ÇODÖ puanları 48.91 (SD: 5.82) idi. Sağlıklı gruba göre otizmli grupta serum TDP-43 ve Serum UCH-L1 düzeyleri anlamlı olarak düşüktü (sırasıyla 506,21±780,97 ng/L ve 1245,80±996,76 ng/L; 3,08±5,44 ng/mL ve 8,64±6,67 ng/mL; p<0.001). Serum TDP-43 and UCH-L1 düzeyleri arasında pozitif korelasyon anlamlı olarak tespit edildi (r=0.947, n= 24, p<0.001).Sonuç: Sonuç olarak, düşük UCHL-L1 ve TDP-43 düzeylerinin, otizmde bozulmuş ubikitinlenme sürecini yansıtabileceği düşünülmüştür.
Düşük serum UCH-L1 ve TDP-43 düzeyleri otizmde bozulmuş ubikuinasyon sürecini yansıtabilir mi?
WOS: 000412669100014
PubMed ID: 29033641
Keywords: Autism; UCH-L1; TDP-43; Ubiquitination; Otizm; UCH-L1; TDP-43; Ubikitinlenme